2020
DOI: 10.1007/s13311-020-00887-6
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Targets: Supraspinal Mechanisms of Analgesia

Abstract: While the acute sensation of pain is protective, signaling the presence of actual or potential bodily harm, its persistence is unpleasant. When pain becomes chronic, it has limited evolutionarily advantage. Despite the differing nature of acute and chronic pain, a common theme is that sufferers seek pain relief. The possibility to medicate pain types as varied as a toothache or postsurgical pain reflects the diverse range of mechanism(s) by which pain-relieving “analgesic” therapies may reduce, eliminate, or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…This was surprising for several reasons. First, the opioid system has a well-established role in pain regulation 53 , 54 and the dopamine system has equally been suggested to be involved in the supraspinal modulation of pain. 55 , 56 Second, alterations in opioid and dopaminergic neurotransmission in chronic pain have been reported in human PET studies.…”
Section: Discussionmentioning
confidence: 99%
“…This was surprising for several reasons. First, the opioid system has a well-established role in pain regulation 53 , 54 and the dopamine system has equally been suggested to be involved in the supraspinal modulation of pain. 55 , 56 Second, alterations in opioid and dopaminergic neurotransmission in chronic pain have been reported in human PET studies.…”
Section: Discussionmentioning
confidence: 99%
“…Activity of ACC neurons is necessary and sufficient for the coding and processing of pain and the accompanying emotional pain, and the balance between neural excitation and inhibition is necessary for the normal function of the ACC ( Gong et al, 2010 ; Zugaib et al, 2014 ). In chronic pain clinical practice and basic research, changes in neurotransmitters in the central system have been found, which was caused by the dysregulation of GABAergic, glutamatergic, dopaminergic and opioidergic mechanisms ( Mhalla et al, 2010 ; Bannister and Dickenson, 2020 ; Yang et al, 2020 ). Dysfunction of GABAergic interneurons, as a major inhibitory system in the central nervous system, was reported to be closely related to the pathogenesis of anxiety-like behavior and chronic pain ( Möhler, 2012 ; Lau and Vaughan, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was surprising for several reasons. First, the opioid system has a well-established role in pain regulation (35,36) and the dopamine system has equally been suggested to be involved in the supraspinal modulation of pain (37,38). Second, alterations in opioid and dopaminergic neurotransmission in chronic pain have been reported in human PET studies (39,40).…”
Section: Discussionmentioning
confidence: 99%